Amos a Commentary based on Amos in Codex Vaticanus. - Glenny, W. Edward (Leiden : BRILL, 2013)
In this commentary Glenny examines the literary features and the Greek text of Amos found in Vaticanus to determine how it would have been understood by early Greek readers who were unfamiliar with the Hebrew.
Preface; Abbreviations; Introduction to the Commentary on Amos; AMOS Text and Translation; Text and Translation; Commentary; Bibliography; Index of References to Ancient Literature; Index of Authors.
Description based on print version record.
Includes bibliographical references and indexes.
Keywords: Bible readings; Bible. -- Amos -- Commentaries; Religion; Bible. -- Commentaries; RELIGION / Biblical Studies / Prophets; Electronic books